Computed Tomographic Findings in Differentiating between Diverticulitis and Colon Cancer - Aphinya Charoensak; Marayart Tongintarach; Nithida Na Songkhla (Siriraj Medical Journal, 2007)
Objective: To determine the computed tomographic (CT) findings associated with diverticulitis or colonic cancer, and to evaluate the CT signs that may help in distinguishing between these two diseases.